1999
DOI: 10.1038/sj.onc.1203024
|View full text |Cite
|
Sign up to set email alerts
|

Implication of mitochondria-derived reactive oxygen species, cytochrome C and caspase-3 in N-(4-Hydroxyphenyl)retinamide-induced apoptosis in cervical carcinoma cells

Abstract: N-(4-Hydroxyphenyl)retinamide (4HPR) is currently used in cancer prevention and therapy trials. It is thought that its e ects result from induction of apoptosis. 4HPR-induced apoptosis in human cervical carcinoma C33A cells involves enhanced generation of reactive oxygen species (ROS). In this study we explored the mechanism by which 4HPR increases ROS and induces apoptosis in these cells. 4HPR induced cytochrome c release from mitochondria to cytoplasm, activated caspase-3, and caused a membrane permeability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
129
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(141 citation statements)
references
References 55 publications
11
129
1
Order By: Relevance
“…4HPR has been described to induce MPT through different mechanisms, which included both ROS and ceramide generation. [46][47][48] However, inhibition of ROS or ceramide production in our cells did not block the apoptosis induced by 4HPR and TRAIL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4HPR has been described to induce MPT through different mechanisms, which included both ROS and ceramide generation. [46][47][48] However, inhibition of ROS or ceramide production in our cells did not block the apoptosis induced by 4HPR and TRAIL.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] TRAIL induces changes in mitochondrial permeability through a different mechanism which involves translocation of the cleaved p15 form of BID into the mitochondrial membrane. As a marker of ROS generation, measurement of DCFH-DA by flow cytometry was used.…”
Section: The Combination Of 4hpr and Trail Induces Caspase-mediated Amentioning
confidence: 99%
“…Retinoids have been reported to increase ROS including superoxide and peroxides in AML cell lines [4,[27][28]. The specific source of ROS in response to ATRA is yet to be determined however, studies by Suzuki et al [29] using the synthetic retinoid, N-(4-hydroxyphenyl) retinamide, showed mitochondrial-mediated ROS generation in cervical carcinoma cells. Also, recent reports have suggested that ROS can modulate signal transduction and activate the NFκB pathway, thereby regulating the process of cell survival among others [30].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, while apoptosis by HPR appears receptor-independent (Delia et al, 1993;Kitareewan et al, 1999), and actually correlates with the ability of HPR to elicit intracellular free radicals and acidi®cation (Delia et al, 1997a;Angoli et al, 1996;Maurer et al, 1999;Suzuki et al, 1999), transcriptional regulation of target genes (e.g. AP1) is retinoid-receptor dependent, according to data showing that HPR selectively activates the transcription by RAR-g, to a less extent by RAR-b, but not by RAR-a (Fanjul et al, 1996;Kazmi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%